COVID-19 infection, quarantine, and sleep disorders: literature review - Sakalauskaitė-Juodeikienė, E. (Neurologijos seminarai, 2020)
It has been known since ancient times that rest and sleep are vital, as are breathing, eating, and other bodily functions. Over the last 30 years, a clear link has been established between adequate sleep and the proper functioning of the immune system. In this article, the author reviews sleep changes caused by viral infection and provides evidence that sleep deprivation acts as a significant factor in functional immunosuppression. The author reviews recent scientific literature suggesting that the administration of melatonin and melatonin receptor agonists for patients with COVID-19 infection treated in the intensive care unit can reduce prevalence of delirium and improve sleep quality, protect patients from “cytokine storm” and improve acute lung injury. Finally, it will be explained how adequate sleep and adherence to sleep hygiene recommendations in this difficult situation can be one of the most important factors regulating our behaviour and emotions and guaranteeing the proper functions of the immune system.
Keywords: sleep disorders; viral infection; acute phase response; COVID-19; melatonin